Development of nutricereals and milk‐based beverage: Process optimization and validation of improved nutritional properties. (14th March 2019) - Kumar, Ashwani; Kaur, Amarjeet; Tomer, Vidisha; Rasane, Prasad; Gupta, Kritika
Abstract: The present study was conducted to develop finger millet and oats based functional beverage. The nutricereals were ground into coarse flour and blended in various proportions (90:10–50:50) to prepare the drink. The functional drink, optimized using response surface methodology, was prepared using malt‐drink (diluted formulation of finger millet: oat in the ratio 60:40) and double toned milk (40:60–60:40). The final optimized product was found to be rich in dietary fibers (1.23%) viz. β‐glucan (101.33 mg/100 mL), and the antioxidants like total polyphenols (52.33 mg/100 mL). The drink was low in fat (1.26%), cholesterol (3.10 mg/100 mL), and lactose (1.75%). Sensory acceptability of the selected beverage (7.21) was at par with the sweetened cattle milk (7.52) on a 9‐point hedonic scale. The overall cost of ready to serve drink was INR 10 (serving size 200 mL), ensuring the economic feasibility of the drink. Practical applications: Finger millet is a rich source of calcium, iron and zinc; and oats are rich in beta‐glucan. Incorporation of finger millet and oats improve the overall functional properties of milk. The complementation of the finger millet with oats can further enhance the physical as well as the functional properties of the milk. The dietary fiber content of the nutricereal based beverage was also increased, which makes it a potential prebiotic. The drink also provides an improved way for the introduction of millets in futuristic food products. Abstract :